Structural Principles in the Development of Cyclic Peptidic Enzyme Inhibitors - Xu, Peng (Int J Biol Sci, 2017)
This review summarizes our studies in the development of small cyclic peptides for specifically modulating enzyme activity. Serine proteases share highly similar active sites but perform diverse physiological and pathological functions. From a phage-display peptide library, we isolated two mono-cyclic peptides, upain-1 (CSWRGLENHRMC) and mupain-1 (CPAYSRYLDC), which inhibit the activity of human and murine urokinase-type plasminogen activators (huPA and muPA) with K(i) values in the micromolar or sub-micromolar range, respectively. The following affinity maturations significantly enhanced the potencies of the two peptides, 10-fold and >250-fold for upain-1 and mupain-1, respectively. The most potent muPA inhibitor has a potency (K(i) = 2 nM) and specificity comparable to mono-clonal antibodies. Furthermore, we also found an unusual feature of mupain-1 that its inhibitory potency can be enhanced by increasing the flexibility, which challenges the traditional viewpoint that higher rigidity leading to higher affinity. Moreover, by changing a few key residues, we converted mupain-1 from a uPA inhibitor to inhibitors of other serine proteases, including plasma kallikrein (PK) and coagulation factor XIa (fXIa). PK and fXIa inhibitors showed K(i) values in the low nanomolar range and high specificity. Our studies demonstrate the versatility of small cyclic peptides to engineer inhibitory potency against serine proteases and to provide a new strategy for generating peptide inhibitors of serine proteases.